2007
DOI: 10.1016/s1578-200x(07)70059-1
|View full text |Cite
|
Sign up to set email alerts
|

18FDG-PET: a new diagnostic approach in hip prosthesis infection

Abstract: Infection following hip arthroplasties can present a diagnostic challenge. No test is 100 % sensitive and 100% specific; this prospective study was undertaken to evaluate the utility of FDG-PET imaging for diagnosing infected joint replacements. 24 hip joint replacements were studied prospectively and we have complete diagnoses with clinical signs and symptoms, laboratory tests, radiography, joint aspiration, radionuclide imaging including FDG-PET, and histopathologic examination. 11 of 24 prostheses were infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…• Joint prosthetic infections (93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109).…”
Section: Common Clinical Indicationsmentioning
confidence: 99%
“…• Joint prosthetic infections (93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109).…”
Section: Common Clinical Indicationsmentioning
confidence: 99%
“…Reviewing titles and abstracts from PubMed/MEDLINE revealed 20 articles potentially eligible for inclusion [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Reviewing titles and abstracts from Embase revealed 17 articles potentially eligible for inclusion, which were all already identified by the PubMed/MEDLINE search.…”
Section: Literature Searchmentioning
confidence: 99%
“…However, this article was excluded because less than 15 patients with hip and/or knee prostheses were investigated [32]. Thus, eventually 11 studies [12,13,15,17,19,20,23,24,27,28,30], comprising a total sample size of 635 prostheses, met all inclusion and exclusion criteria, and they were included in this systematic review. The characteristics of the included studies are presented in Tables 3, 4, and 5.…”
Section: Literature Searchmentioning
confidence: 99%
“…Stumpe et al [50] and Love et al [24] reported accuracies of only 69% and 71% in diagnosing lower joint infections with 18 F-FDG, respectively. In addition, Garcia-Barrechguren et al [51] demonstrated a sensitivity and specificity of 64% and 67%, respectively in patients being tested for prosthetic hip infection. Moreover, Stumpe et al [52] and Delank et al [53] concluded in their studies that 18 F-FDG PET is not specific for infection.…”
Section: Originalmentioning
confidence: 99%